Henri Chopin en guises d'autobiographie forcément incomplète : a sort of autobiography inevitably incomplete - Chopin, Henri 1922-2008 (LemonMelon, 2015)
"... A publication based on an autobiographical text written in 1992 by Henri Chopin, one of the most influential experimental sound and performance artists of the twentieth century. It includes previously unpublished black and white photographs of the artist's life, his performances and publications. It also contains a full colour plate section of some of his most pivotal works"--LemonMelon Web site
"On the occasion of Frieze Masters Spotlight 2015"--Colophon
Keywords: Chopin, Henri / Exhibitions; Chopin, Henri -- 1922-2008; Geschichte 1900-2000; Poets, French / 20th century / Biography; Performance artists / France / Biography; Artists' books / France; Experimental poetry, French; Sound poetry / France; Frankreich; Ausstellungskatalog; Ausstellungskatalog -- Gloucester Green, Regent's Park -- 14.10.2015-18.10.2015 -- London; Biografie